IMPLEMENTATION OF THE DUAL EDUCATION SYSTEM IN TECHNICUM-LEVEL INSTITUTIONS: A COMPETENCY-BASED APPROACH TO INTEGRATING ACADEMIC LEARNING WITH INDUSTRIAL PRACTICE (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The contemporary landscape of vocational education is characterized by a growing disconnect between formal academic preparation and the practical competency demands of an increasingly dynamic labor market. This article addresses the structural inefficiency of theory-dominant instruction in technicum-level institutions (TLIs) and proposes the “Dual Education System” as a strategic mechanism for curriculum-practice transformation. By integrating educational institutions, industrial enterprises, and state regulatory bodies into a unified ecosystem, the dual model aims to harmonize learning outcomes with employer expectations and strengthen the long-term employability of graduates.